2018
DOI: 10.5271/sjweh.3728
|View full text |Cite
|
Sign up to set email alerts
|

Night work and hypertensive disorders of pregnancy: a national register-based cohort study

Abstract: Objective The aim of this study was to investigate whether night work expressed by number and duration of night shifts, number of consecutive night shifts, and number of quick returns during the first 20 weeks of pregnancy is a risk factor for hypertensive disorders of pregnancy (HDP). Methods The study population comprised Danish workers in public administration and hospitals who gave birth between 2007 and 2013. Exposure was assessed objectively through payroll data. Information on the outcome was retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 51 publications
(68 reference statements)
1
25
0
7
Order By: Relevance
“…In a recent published study using the same source population as in the present study, we found that women with longer spells of consecutive night shifts, and among obese women also those with long night shifts and quick returns, during the first 20 pregnancy weeks had increased risk of hypertensive disorders 22. Field studies have shown increasing hormonal dysfunction with increasing number of consecutive night shifts 37–39.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a recent published study using the same source population as in the present study, we found that women with longer spells of consecutive night shifts, and among obese women also those with long night shifts and quick returns, during the first 20 pregnancy weeks had increased risk of hypertensive disorders 22. Field studies have shown increasing hormonal dysfunction with increasing number of consecutive night shifts 37–39.…”
Section: Discussionsupporting
confidence: 69%
“…The study cohort was retrieved from the same source population as in a recently published study 22. In short, it comprised 42 485 women from the DWHD who gave birth at least once during from January 2007 to December 2013, giving a total of 60 482 pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to shift work in women, shift workers may have increased rates of menstrual disruption and night shifts may be associated with increased rates of spontaneous abortion . However, whether these results are applicable to other settings remains controversial as another study showed no significant increase in miscarriage rates among shift work nurses .…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, evidence has been accumulating from systematic reviews, meta-analyses, and register-based prospective cohort studies about obstetric outcomes of pregnant workers. [9][10][11][12][13] With respect to shift work in women, shift workers may have increased rates of menstrual disruption and night shifts may be associated with increased rates of spontaneous abortion. 9,10,12,13 However, whether these results are applicable to other settings remains controversial as another study showed no significant increase in miscarriage rates among shift work nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation